1997
DOI: 10.12968/jowc.1997.6.5.213
|View full text |Cite
|
Sign up to set email alerts
|

Management of a fungating breast wound

Abstract: This case report provides an outline and brief background to current treatment options and details the management of a patient with a novel hydrogel dressing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Six research-based articles on malignant fungating wounds were found (Grocott, 1997, Thomas et al 1998, Haisfield-Wolfe & Baxendale-Cox 1999, Grocott 2000, Grocott & Cowley 2001, and showed that most guidelines on malignant fungating wounds were developed through experience rather than based on clinical intervention research. Ten were case studies that documented individual trials (Shutler et al 1997, Jones 1998, Price 2000. The identified articles describe, primarily, the physiological consequences of living with a cancer-related wound, including wound related pain (Hallet 1995), exudation (Grocott 2000), infection (Morison et al 1997), bleeding (Haisfield-Wolfe & Rund 1997) and malodour (Haughton & Young 1995, Price 1996, Mallett et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six research-based articles on malignant fungating wounds were found (Grocott, 1997, Thomas et al 1998, Haisfield-Wolfe & Baxendale-Cox 1999, Grocott 2000, Grocott & Cowley 2001, and showed that most guidelines on malignant fungating wounds were developed through experience rather than based on clinical intervention research. Ten were case studies that documented individual trials (Shutler et al 1997, Jones 1998, Price 2000. The identified articles describe, primarily, the physiological consequences of living with a cancer-related wound, including wound related pain (Hallet 1995), exudation (Grocott 2000), infection (Morison et al 1997), bleeding (Haisfield-Wolfe & Rund 1997) and malodour (Haughton & Young 1995, Price 1996, Mallett et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…1998, Haisfield‐Wolfe & Baxendale‐Cox 1999, Grocott 2000, Grocott & Cowley 2001), and showed that most guidelines on malignant fungating wounds were developed through experience rather than based on clinical intervention research. Ten were case studies that documented individual trials (Shutler et al. 1997, Jones 1998, Price 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach had not been evaluated formally. Thirdly, although the role of wound dressings was emphasized, published case histories demonstrated a mismatch between the design of wound dressings and the size, severity and location of the wounds, and identified a need to explore novel approaches to dressing the wounds (Neal, 1991;Saunders, 1997;Shutler et al, 1997;Sweeney et al, 1998). The research questions and study aims developed logically from these three issues.…”
Section: Purpose and Backgroundmentioning
confidence: 99%